Impact of Volumetric Changes in the Upper Airways after Orthognathic Surgery: Study Pilot - Soares, Cauê Fontan; Aguiar, Priscila Lins; Lago, Carlos Augusto Pereira do; Silva Neto, Joaquim Celestino da (ARCHIVES OF HEALTH INVESTIGATION, 2024)
OBJECTIVE: The aim of the present study was to assess volumetric changes in the upper airways of patients submitted to orthognathic surgery and the impact on quality of life. METHODS: The study evaluated clinical and psychosocial aspects of patients undergoing orthognathic surgery at Hospital Getúlio Vargas in the city of Recife, Brazil, in 2019 and 2020. A prospective longitudinal study pilot was carried out. Quality of life, self-esteem, obstructive sleep apnea syndrome symptoms and upper airway volume changes were assessed preoperatively and over one year postoperatively. RESULTS: Eight patients (three men and five women) agreed to participate in the study and answered the questionnaires in the preoperative and postoperative periods. Three were between 18 and 24 years of age and five were between 25 and 44 years of age. Half of the patients had the long face pattern (50%) and most had occlusal pattern III (87.5%). Although the average volume and minimum cross-sectional area had diminished in the overall sample, a reduction occurred in signs and symptoms of obstructive sleep apnea syndrome. Surgery also had a strong impact on quality of life assessed using the OHIP-14 and orthognathic quality of life questionnaire. CONCLUSION: Orthognathic surgery exerts a positive impact on quality of life and self-esteem. However, airway size is not a determinant of this improvement.